Development of a problem based learning teaching module on the human respiratory system for class XI high school students - Hassan, Arika Azmi; Yusuf, Frida Maryati; Ibrahim, Mustamin; Solang, Margaretha; Mamu, Hartono D. (Univeritas Papua, 2025)
This study aims to address the validity, practicality, and student learning outcomes utilising a Problem-Based Learning (PBL) teaching module on the human respiratory system. The study adopted the Research and Development (R&D) method, employing the ADDIE model limited to the development stage with small-scale trials. The trial subjects consisted of 24 students from Class XI IPA 3 at SMA Terpadu Wira Bhakti Gorontalo for the 2024/2025 academic year. The instruments used are validation sheets, student response questionnaires, and learning outcomes tests. The research results show that in the validation test the teaching module obtained an average percentage of 87% (very valid), the student worksheet scored 78% (valid), and the test instrument scored 84% ​​(very valid). The students' response obtained an average percentage of 91.87% (very good). Analysis of learning outcomes shows an average N-Gain of 0.8 (high category). Thus, it shows that the PBL-based teaching module developed has met the valid and practical criteria so that it is suitable for use as a learning support to improve student learning outcomes in the human respiratory system material in class XI high school students.